Three-loop uncertainties compensator and sliding mode quadrotor control. (January 2020) - Alqaisi, Walid; Ghommam, Jawhar; Alazzam, Anas; Saad, Maarouf; Nerguizian, Vahé
Abstract : In this paper, a Three Loop Uncertainties Compensator (TLUC) and Exponential Reaching Law Sliding Mode Controller (ERSM) is proposed and successfully applied to an Unmanned Aerial Vehicles (UAV) quadrotor. The TLUC estimates unknown time-varying uncertainties and perturbations to reduce their effects and to preserve stability. The ERSM is integrated based on the Lyapunov stability theory to obtain fast responses with the lowest possible chattering. The novelty of this paper is that the TLUC can estimate and compensate for uncertainties and unknown time-varying disturbances in three loops. This provides tracking of residual uncertainty to provide a higher level of support to the controller. The performance is verified through analyses, simulations and experiments.